Multicausal factors underlying post-hajj oxygen desaturation: a case-based analysis from two elderly pilgrims at the 2025 surabaya debarkation - Gustaf, Aridin; Griana, Tias Pramesti (Proceeding Annual Symposium on Hajj and Umrah Medicine; Vol 3 (2025): Proceeding Annual Symposium on Hajj and Umrah MedicineDO - 10.18860/anshar.v3i0.3680, 2026)
Oxygen desaturation is a significant clinical concern among Hajj pilgrims, particularly in older adults with comorbidities such as lower respiratory tract infections. Prolonged travel, exposure to extreme environmental conditions, and immune decline during pilgrimage substantially contribute to respiratory compromise. This report describes two elderly pilgrims who developed oxygen desaturation upon arrival at the Surabaya debarkation site in 2025. The first patient, an 88-year-old woman, presented with desaturation following the pilgrimage and was diagnosed with community-acquired pneumonia after hospitalization at King Abdul Aziz Hospital, Mecca. The second patient, a 75-year-old woman with no prior comorbidities, developed mild desaturation suspected to be due to bronchopneumonia following high-risk environmental exposure during the pilgrimage. Contributing factors included advanced age, prolonged air travel, exposure to extreme temperatures, post-hospital immobility, and dehydration. These cases highlight that post-Hajj desaturation is multifactorial and predominantly affects elderly pilgrims. Early identification, comprehensive pre-departure health screening, continuous monitoring during and after pilgrimage, and implementation of early detection systems at debarkation sites are essential to prevent severe complications and reduce morbidity among returning pilgrims.